Evaluation of paper-based and web-based food frequency questionnaires for 7-year-old children in Singapore. Issue 8 (28th October 2022) - Lai, Jun S.; Loh, Jason; Toh, Jia Ying; Sugianto, Ray; Colega, Marjorelee; Tan, Kok Hian; Yap, Fabian Kok Peng; Chong, Yap-Seng; Godfrey, Keith M.; Chong, Mary Foong-Fong
Abstract: Advances in technology enabled the development of a web-based, pictorial FFQ to collect parent-report dietary intakes of 7-year-old children in the Growing Up in Singapore Towards healthy Outcomes study. This study aimed to compare intakes estimated from a paper-FFQ and a web-FFQ and examine the relative validity of both FFQ against 3-d diet records (3DDR). Ninety-two mothers reported food intakes of their 7-year-old child on a paper-FFQ, a web-FFQ and a 3DDR. A usability questionnaire collected participants' feedback on the web-FFQ. Correlations and agreement in energy, nutrients and food groups intakes between the dietary assessments were evaluated using Pearson's correlation, Lin's concordance, Bland–Altman plots, Cohen's κ and tertile classification. The paper- and web-FFQ had good correlations (≥ 0·50) and acceptable-good agreement (Lin's concordance ≥ 0·30; Cohen's κ ≥ 0·41; ≥ 50 % correct and ≤ 10 % misclassification into same or extreme tertiles). Compared with 3DDR, both FFQ showed poor agreement (< 0·30) in assessing absolute intakes except micronutrients (web-FFQ had acceptable-good agreement), but showed acceptable-good ability to classify children into tertiles (κ ≥ 0·21; ≥ 40 % and ≤ 15 % correct or misclassification). Bland–Altman plots suggest good agreement between web-FFQ and 3DDR in assessing micronutrients and several food groups. The web-FFQ was well-received, and majority (81 %) preferred the web-FFQ over the paper-FFQ. The newly developed web-FFQ produced intake estimates comparable to the paper-FFQ, has acceptable-good agreement with 3DDR in assessing absolute micronutrients intakes and has acceptable-good ability to classify children according to categories of intakes. The positive acceptance of the web-FFQ makes it a feasible tool for future dietary data collection.